Non-prescription medicines and Australian community pharmacy interventions: rates and clinical significance - Williams, K.; Emmerton, Lynne; Taylor, R.; Werner, J.; Benrimoj, S. (Pharmaceutical Press, 2011)
Objective: To quantify pharmacy intervention rates for non-prescription medications (pharmacist-only and pharmacy medicines), to document the clinical significance of these interventions and to determine the adverse health consequences and subsequent health care avoided as a result of the interventions. Methods: Non-prescription medicines interventions undertaken by community pharmacy staff were recorded in two field studies: a study of all Australian pharmacies to determine incidence rates for low-incidence, highly significant interventions, and a study of a sample of pharmacies to collect data on all non-prescription interventions. Recorded interventions were assessed by a clinical panel for clinical significance, potential adverse health consequence avoided, probability and likely duration of the adverse health consequence.Key findings: The rate of professional intervention that occurs in Australia for pharmacist-only and pharmacy medicines is 5.66 per 1000 unit sales (95% confidence interval 4.79–6.64). Rates of intervention varied by clinical significance. When considering health care avoided, the main impact of the interventions was avoidance of urgent general practitioner (GP) visits, followed by avoidance of regular GP visits and accident and emergency treatment. The most common adverse health consequences avoided were exacerbations of an existing condition (e.g. hypertension, asthma) and adverse drug effects. Conclusions: This study demonstrates the way in which community pharmacy encourages appropriate non-prescription medicine use and prevents harm through intervening at the point of supply. It was estimated that Australian pharmacies perform 485 912 interventions per annum when dealing with non-prescription medicines, with 101 324 per annum being interventions that avert emergency medical attention or serious harm, or which are potentially life saving.